Idiom och semantisk variation – i autentiskt språkbruk och i ordböcker1 - Sköldberg, Emma (Nordiske Studier i Leksikografi, 2006)
Idiom and semantic variation in authentic usage and dictionaries. This paper explores the meanings of Swedish idioms in authentic texts and how they are reflected in dictionaries. More specifically, I recount the relationship between the meanings of 36 idioms expressed in a large collection of press material and the idiomatic meanings given in four Swedish monolingual dictionaries of partially divergent type. The study shows that a large number of idioms are defined in a variety of ways under different lemmas in the same dictionary, although the definitions must be regarded as correct in the absolute majority of cases. This applies primarily to expressions that provide a uniform impression in the press material from the semantic perspective. Several idioms whose semantic variation is more apparent in authentic texts could, on the other hand, be more perfectly described. Specimens of speech and usage notes could also be used more extensively to illustrate the meanings of idioms.